Antimicrobial and antimalarial properties of medicinal plants used by the indigenous tribes of Andaman and Nicobar Islands, India. (July 2016) - Chander, M. Punnam; Pillai, C.R.; Sunish, I.P.; Vijayachari, P.
Abstract: In this study, methanol extracts of six medicinal plants ( Alstonia macrophylla, Claoxylon indicum, Dillenia andamanica, Jasminum syringifolium, Miliusia andamanica and Pedilanthus tithymaloides ) traditionally used by Nicobarese tribes of Andaman and Nicobar Islands were studied for antimicrobial and antimalarial activities as well as preliminary photochemical analysis. Plants were collected from Car Nicobar of Andaman and Nicobar Islands and the ethnobotanical data were gathered from traditional healers who inhabit the study area. The methanol extracts were obtained by cold percolation method and the antimicrobial activity was found using agar well diffusion method. Among the plants tested, J. syringifolium, D. andamanica, C. indicum were most active. The antimalarial activity was evaluated against Plasmodium falciparum chloroquine-sensitive MRC-2 isolate. The crude extract of M. andamanica showed excellent antimalarial activity followed by extracts of P. tithymaloides, J. syringifolium and D. andamanica . The chemical injury to erythrocytes was also carried out and it showed that, there were no morphological changes in erythrocytes by the methanol crude extracts. The in vitro antimicrobial and antimalarial activity might be due to the presence of alkaloids, flavonoids, triterpenes, sterols, tannins and saponins in the methanol extracts of tested plants. Highlights: Nicobarese are among the six indigenous tribes of Andaman and Nicobar Islands, India. Six medicinal plants were selected for evaluation on the basis of their ethnomedicinal use. Miliusia andamanica and Dillenia andamanica are endemic to Andaman and Nicobar Islands. M. andamanica, Jasminum syringifolium and Pedilanthus tithymaloides possess significant suppressive effects on in-vitro cultures.